Whey as a sustainable binder for the production of extruded activated carbon. Issue 3 (June 2022) - Llamas-Unzueta, Raúl; Montes-Morán, Miguel A.; Ramírez-Montoya, Luis A.; Concheso, Alejandro; Menéndez, J. Angel
Abstract: Whey, the main by-product of the dairy industry, is proposed as a sustainable binder for the production of extruded activated carbon. Coconut shell char was mixed with controlled quantities of either rehydrated whey powders or partially dehydrated liquid whey. After extrusion, extrudates were dried, and carbonised or activated under N2 or CO2 atmosphere, respectively. A comprehensive study of the effect of different parameters including binder proportion, coconut shell char particle size and carbonisation temperature was carried out. The composition of whey prompted Maillard reactions boosted with temperature that conferred a resin-like behaviour to the binder. Quality parameters of the resulting extrudates were their ball-mill hardness, real and bulk densities. All whey-bound pellets retained their original shape after the high temperature treatment. The hardness of those whey extrudates was particularly remarkable considering the biomass origin of this binder. The carbonisation temperature had little effect in the hardness or densities of the carbon pellets. The best pellet formulation comprised the use of coconut shell char powders with particle sizes < 212 µm, in mixtures having a 7/3 char/dry whey mass ratio. The properties of the pellets obtained after the activation of such pellets were comparable to those of commercial activated carbon extrudates. The use of partially dehydrated liquid whey rather than re-hydrated dry whey rendered very similar results. The alkalinity of the binder made the resulting activated carbons adequate for H2 S removal at room temperature. An economic estimation of the process placed whey in a practical position within the binder market. Graphical Abstract: ga1 Highlights: Whey is a good and sustainable binder for the manufacture of extruded activated carbons. Pellets made with whey have porosities and friability similar to commercial pellets. Dried whey and liquid whey produce extrudates of similar quality. Pellets made with whey have a good performance for H2 S removal from gas streams. The use of whey as a binder is a plausible alternative for its valorisation.